Solar energy utilisation in Australian homes: A case study - Ramadas Narayanan (Elsevier, 2021)
With limited roof space available, the selection of the most suitable solar energy systems to meet hot water and electricity demands for a household in a cost-effective way is always a challenge. This paper presents a comparative study of solar energy collection methods to meet Australian household's energy demands using both solar thermal collectors and photovoltaic (PV) systems. Numerical models are developed for various system configurations and two different scenarios are analysed in this research. In the first scenario, only PV system is used to meet both hot water and electricity demands. In the second, both the solar thermal collectors and solar PV system are used in combination for the same roof area. Based on the modelling results, economic benefits are determined and compared. The combined system was found to be a better option, providing greater benefits in cost and emission reduction.